Relavansi ISR sebagai mediasi hubungan Intectual capital terhadap profitabilitas - Supami, Setiyowati Wahyu; Mardiana, Mardiana (IQTISHODUNA, 2024)
Profitability is the financial performance of a company. The financial performance of Islamic banking shows its potential to generate profits while utilizing the resources it has. The aim of this research is to determine the impact of intellectual on profitability mediated by corporate social responsibility. The population used is sharia banks in the 2017-2023 Financial Services Authorization. The sampling technique used was proportional sampling. The total sample is 5 sharia banks. Multiple linear regression using SPSS is used in the data analysis method. The test's findings indicate that intellectual capital and profitability are related. Social responsibility is influenced by intellectual capital. Profitability is impacted by social responsibility. Through social responsibility, intellectual capital affects profitability. The implication of this research is that sharia banking must increase intellectual capital and increase social responsibility optimally to obtain value from investors and potential investors.